Analisis Kekuatan Struktur pada Kondisi Lifting dengan menggunakan Dua Crane (Studi Kasus: Module Gas Compressor Project FPSO Marline Natuna, Batam) - Edi Junaedi; Era Agita Kabdiyono (Jurnal Teknik dan Science, 2026)
Lifting is a common activity in fabrication and construction processes. It is a hazardous activity; failure during the lifting process can cause permanent damage to the products or structures being worked on. Furthermore, failure during the lifting process can endanger worker safety and even jeopardize the entire project. Lifting operations require not only calculations of the lifting equipment’s capacity—such as cranes and supporting tools like slings and shackles—but also an assessment of structural strength. Therefore, structural analysis under lifting conditions is essential; errors in planning can have severe consequences for the project. The planning stages are carried out using STAADpro software, starting from geometric modeling through to inputting parameters in accordance with applicable standards and regulations, such as the load magnification factor specified in DNVGL-ST -N001 Marine Operations and Marine Warranty, and the results of the analysis using STAADpro are re-verified through manual calculations in accordance with SNI 1729-2020 Specifications for Structural Steel Buildings. This verification process is carried out to ensure that the numerical analysis results obtained meet the requirements for strength, stability, and structural performance in accordance with design standards.